The merger delusion : how swallowing its suburbs made an even bigger mess of Montreal - Trent, Peter (Peter F.) (desLibris. Books collection., 2012)
Powerless under the country's constitution, Canadian municipal governments often find themselves in conflict with their provincial masters. In 2002, the Province of Quebec forcibly merged all cities on the Island of Montreal into a single municipality - a decision that was partially reversed in 2006. The first book-length study of the series of mergers imposed by the Parti Québécois government, The Merger Delusion is a sharp and insightful critique by a key player in anti-merger politics. Peter Trent, mayor of the City of Westmount, Quebec, foresaw the numerous financial and institutional problems posed by amalgamating municipalities into megacities. Here, he presents a stirring and detailed account of the battle he led against the provincial government, the City of Montreal, the Board of Trade, and many of his former colleagues. Describing how he took the struggle all the way to the Supreme Court of Canada, Trent demonstrates the ways in which de-mergers resonated with voters and eventually helped the Quebec Liberal Party win the 2003 provincial election. As the cost and pitfalls of forced mergers become clearer in hindsight, The Merger Delusion recounts a compelling case study with broad implications for cities across the globe.